Cultura' pedagógica: a influência do status do professor - Dourado, Maria Lucia Goulart (1979)
It was the aim of this study to investigate the creation of a pedagogical 'culture', with and without the influence of the teacher who is subject to an institutionally defined status. Therefore, an experimental setting was devised with the subjects distributed in two types of groups, one typpe for controlling and another for experiment itself. In the second group a teacher was included and she had been previously instructed to influence the subjects. According to this strategy, the subjects performed the Decision Teste by Consensus by means of interpretations and classifications which were taken as 'culture' created by the groups with and without the teacher's influence. The empirical data collected and analyse according to the Phenomenological Approach led us to the conclusion that the teacher's r ole is crucial in the influence of the students behaviour and that this influence can be attributed moostly to the status conferred on him. Furthermore, the literature consulted allowed a critical analysis of the modeler role performed by the teacher (Modernizing Approach) as well as an analysis of the dominant culture reproduction process implicit in this role (Alternative Approach). Thus, the empirical data and the theories analysed led us to conclude that the pedagogical 'culture' created as well in the presence of as in the absence of the teacher is neither neutral nor apolitical.